2019
DOI: 10.7554/elife.47098
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for DNA-mediated nuclear compartmentalization distinct from phase separation

Abstract: RNA Polymerase II (Pol II) and transcription factors form concentrated hubs in cells via multivalent protein-protein interactions, often mediated by proteins with intrinsically disordered regions. During Herpes Simplex Virus infection, viral replication compartments (RCs) efficiently enrich host Pol II into membraneless domains, reminiscent of liquid-liquid phase separation. Despite sharing several properties with phase-separated condensates, we show that RCs operate via a distinct mechanism wherein unrestrict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
259
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(283 citation statements)
references
References 51 publications
(91 reference statements)
23
259
0
1
Order By: Relevance
“…2B, C), demonstrating that this treatment does not interfere with direct binding to DNA. This observation is consistent with results from human cells, in which hexanediol does not disrupt nonspecific DNA binding of RNA polymerase II (51).…”
Section: Rnap Clustering Is Mediated By Protein-protein Interactionssupporting
confidence: 91%
See 2 more Smart Citations
“…2B, C), demonstrating that this treatment does not interfere with direct binding to DNA. This observation is consistent with results from human cells, in which hexanediol does not disrupt nonspecific DNA binding of RNA polymerase II (51).…”
Section: Rnap Clustering Is Mediated By Protein-protein Interactionssupporting
confidence: 91%
“…Despite this exciting progress, it remains challenging to study phase separation in any organism but particularly in bacteria. Indeed, while the appearance of fluorescent foci in cells is promising, this alone is not compelling evidence for LLPS because foci can form through many alternative mechanisms (51). So additional tools for interrogating putative condensates are urgently needed.…”
Section: Single-molecule Tracking As a Tool For Examining Llps In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was recently demonstrated that HSV-1 VRCs are not disrupted by treatment with 1,6-hexanediol, which is a feature of many other cellular BMCs. Moreover, the authors report that the recruitment of RNA polymerase II (RNAP II) to VRCs and its movement within VRCs are best explained by a model other than LLPS [105]. However, the role of LLPS in biological processes can be subtle and complex.…”
Section: Biophysical Processes In Replication Compartment Formationmentioning
confidence: 99%
“…Notably, during latency key lytic promoters like RTA contain both the activating H3K4me3 and the repressive H3K27me3 histone marks, representing a 'poised' state [53]. At later stages of infection, KSHV, EBV and HSV-1 genomes have been shown to be largely nucleosome free, consistent with histones not being packaged in virions [33,35,54,55]. At later stages of infection, KSHV, EBV and HSV-1 genomes have been shown to be largely nucleosome free, consistent with histones not being packaged in virions [33,35,54,55].…”
Section: Discussionmentioning
confidence: 99%